2021
DOI: 10.1007/s12640-021-00428-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Combined Administration of 1MeTIQ and MK-801 on Cell Viability, Oxidative Stress Markers, and Glutamate Release in the Rat Hippocampus

Abstract: MK-801, as an N-methyl-D-aspartate (NMDA) receptor inhibitor, causes elevation in glutamate release, which may lead to an increase in excitotoxicity, oxidative stress and, consequently, cell death. 1-Methyl-1,2,3,4-tetrahydroisoquinoline (1MeTIQ) shows antioxidant activity. The aim of the present study was to evaluate the effect of combined treatment with 1MeTIQ and MK-801 on cell viability, antioxidant enzyme activity, and glutamate release in the rat hippocampus. Cytotoxicity was measured using lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
4
0
3
Order By: Relevance
“…La hipofunción en estos receptores se asocia con alteraciones en la memoria, cognición y plasticidad neuronal, y con alteraciones en la liberación de glutamato en estructuras neuronales específicas, como el hipocampo y la corteza frontal. 48 Con base en esto, en este estudio se utilizó el modelo de administración aguda de MK-801 en ratones según la metodología reportada por Aquino-Miranda et al, 8 ya que se trata de un modelo estandarizado y reproducible que causa una hipofunción glutamatérgica, estrés oxidativo y muerte celular, tal como se observa en la esquizofrenia. 48 Reportamos un incremento de la lipoperoxidación en el grupo con MK-801 que fue tratado con vehículo, demostrando que el MK-801 incrementa el estrés oxidante y el daño a las membranas celulares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La hipofunción en estos receptores se asocia con alteraciones en la memoria, cognición y plasticidad neuronal, y con alteraciones en la liberación de glutamato en estructuras neuronales específicas, como el hipocampo y la corteza frontal. 48 Con base en esto, en este estudio se utilizó el modelo de administración aguda de MK-801 en ratones según la metodología reportada por Aquino-Miranda et al, 8 ya que se trata de un modelo estandarizado y reproducible que causa una hipofunción glutamatérgica, estrés oxidativo y muerte celular, tal como se observa en la esquizofrenia. 48 Reportamos un incremento de la lipoperoxidación en el grupo con MK-801 que fue tratado con vehículo, demostrando que el MK-801 incrementa el estrés oxidante y el daño a las membranas celulares.…”
Section: Discussionunclassified
“…48 Con base en esto, en este estudio se utilizó el modelo de administración aguda de MK-801 en ratones según la metodología reportada por Aquino-Miranda et al, 8 ya que se trata de un modelo estandarizado y reproducible que causa una hipofunción glutamatérgica, estrés oxidativo y muerte celular, tal como se observa en la esquizofrenia. 48 Reportamos un incremento de la lipoperoxidación en el grupo con MK-801 que fue tratado con vehículo, demostrando que el MK-801 incrementa el estrés oxidante y el daño a las membranas celulares. Estos hallazgos concuerdan con lo reportado en el estudio de Ozyurt et al, 49 en el cual la administración del MK-801 por vía intraperitoneal en ratas incrementó el estrés oxidante en la corteza frontal, observándose un aumento de la lipoperoxidación.…”
Section: Discussionunclassified
“…On the contrary, the combined treatment of 1MeTIQ and MK-801 showed promising results in mitigating glutamate-induced neurotoxicity. 74 MK-801, known for its NMDA receptor inhibition, triggered glutamate release and oxidative stress, leading to cell death. However, coadministration of 1MeTIQ effectively attenuated these toxic effects, demonstrating its potential as a neuroprotective agent.…”
Section: Neuroprotection Through Targeted Interventionsmentioning
confidence: 99%
“…Increased subcortical DA release and related behavior are thought to serve as an experimental model of positive schizophrenia symptoms [ 116 ]. Further studies have shown that injection of MK-801 also leads to an increase in GLU efflux in the hippocampus and medial prefrontal cortex [ 117 , 118 , 119 ]. Regarding the role of the GLUergic system in schizophrenia pathophysiology, excessive GLU efflux in regions such as the prefrontal cortex and hippocampus is believed to produce symptoms of the illness, mainly cognitive symptoms [ 120 ].…”
Section: Pharmacological Modelsmentioning
confidence: 99%
“…These effects may result in an increased cellular oxidative stress response [ 133 ], which is a widely studied feature of schizophrenia [ 134 , 135 ]. MK-801 has been shown to induce oxidative stress, including elevated MDA levels and altered antioxidant enzyme activity, in several brain regions in rodents, such as the prefrontal cortex, hippocampus, retrosplenial/posterior cingulate cortex [ 119 , 136 , 137 ], and cultured neurons and glial cells [ 138 , 139 ]. Additionally, MK-801 decreases GSH, a main antioxidative compound, leading to a reduced capacity to protect brain cells against oxidative stress [ 140 , 141 ].…”
Section: Pharmacological Modelsmentioning
confidence: 99%